Food Sovereignty Indicators for Indigenous Community Capacity Building and Health - Blue Bird Jernigan, Valarie; Maudrie, Tara L.; Nikolaus, Cassandra Jean; Benally, Tia; Johnson, Selisha; Teague, Travis; Mayes, Melena; Jacob, Tvli; Taniguchi, Tori (Frontiers in Sustainable Food Systems, 2021)
Food insecurity, defined as a lack of stable access to sufficient and nutritious food, is a global public health priority due to its relationships with diminished mental and physical human health. Indigenous communities experience disproportionality high rates of food insecurity as a byproduct of settler-colonial activities, which included forced relocation to rural reservation lands and degradation of traditional subsistence patterns. Many Indigenous communities have worked to revitalize their local food systems by pursuing food sovereignty, regularly expressed as “the right of people to have access to healthy and culturally appropriate foods, while defining their own food systems.” However, little existing guidance is available to assess a community’s ongoing efforts for food sovereignty from a community-wide food systems perspective. The purpose of this review was to describe the scientific literature and identify key Indigenous food sovereignty indicators that may support public health. The seven indicators are: 1) access to resources, 2) production, 3) trade, 4) food consumption, 5) policy, 6) community involvement, and 7) culture. A total of 25 sub-indicators are outlined to allow communities to understand how an indicator is operationalized as well as explore their own community’s progress within each indicator. It is not expected that every indicator and their subcategories will apply fully to any given Indigenous community, but that these indicators should provide a valuable guide to building and assessing efforts to create sustainable and sovereign Indigenous food systems.